2016
DOI: 10.1136/bjophthalmol-2015-308062
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure elevation and choroidal thinning

Abstract: Choroidal thickness in the subfoveal region and in the peripapillary region decreased parallel to an acute increase in IOP in individuals 2 h after a dark room test. Choroidal thickness depends on the actual IOP, which may be noted when choroidal thickness is measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
3
16
1
Order By: Relevance
“…Such a finding would agree with a previous histomorphometric study in which the choroid was significantly thinner in eyes with chronic angle-closure glaucoma than in a control group 30 . It would also agree with a recent investigation in which eyes with increases in intraocular pressure in a dark room adaptation test showed thinning of the choroid 31 . This finding is also in partial contrast to the results of studies on eyes with acute angle-closure glaucoma in which an abnormally thick choroid was reported 9 , 10 .…”
Section: Discussionsupporting
confidence: 93%
“…Such a finding would agree with a previous histomorphometric study in which the choroid was significantly thinner in eyes with chronic angle-closure glaucoma than in a control group 30 . It would also agree with a recent investigation in which eyes with increases in intraocular pressure in a dark room adaptation test showed thinning of the choroid 31 . This finding is also in partial contrast to the results of studies on eyes with acute angle-closure glaucoma in which an abnormally thick choroid was reported 9 , 10 .…”
Section: Discussionsupporting
confidence: 93%
“…The observation made in our study, however, fits with the result of a recent study on patients who developed an increased intra‐ocular pressure after spending 2 hr in a dark room adaptation test and who showed a thinning of the choroid (Wang et al. ). The finding that the neither SMVL‐to‐LVL thickness ratio nor the thickness of the choroidal layers taken separately were significantly associated with the prevalence of open‐angle glaucoma, AMD, DR and retinal vein occlusions supports the notion that peripapillary choroidal thickness may not be correlated with the prevalence of these disorders (Xu et al.…”
Section: Discussionsupporting
confidence: 92%
“…All these factors may exert an effect on the results obtained. Many studies confirmed the effect of such factors as age, gender, axial length of the eye (AL), refraction defect, CCT, or the IOP level of the choroidal thickness [ 30 32 ]. A comprehensive study concerning the evaluation of the subfoveal choroidal thickness (SFCT) which covered 3,233 patients showed that the SFCT is higher in younger individuals, in shorter eyeballs, in males, in eyes with a deeper anterior chamber, thicker lens, flat retina, and better best corrected visual acuity (BCVA).…”
Section: Discussionmentioning
confidence: 99%